sebuah HUBUNGAN KECEMASAN DENGAN ORAL CANDIDIASIS PADA LANSIA DI PANTI PANGESTI LAWANG. - wibowo wibowo (Jurnal Keperawatan Malang, 2019)
Anxiety is one of the factors in the decrease in salivary production, this is caused by the emotional state of the autonomic nervous system will hinder the sympathetic nervous system in salivary secretion. this will result in decreased components and the amount of saliva so that the function of saliva as a defense of the oral mucosa is disrupted, so that it will increase the risk of infection in the oral cavity, one form of infection is oral candidiasis. The method in this research is correlation research with case control (retrospective) design. The study population was elderly in the 60-year-old Pangesti Lawang Orphanage. A sample of 36 respondents was selected using purposive sampling technique. In this study, researchers used two HARS Hamilton Rating Scale for Anxiety measures to measure anxiety and an oral observation sheet of Candidiasis was used to observe the signs and symptoms of oral Candidiasis. Data processing and analysis using the Spearman correlation test and logistic regression test The results showed that the correlation coefficient of 0.376 with a significance value of 0.024 (p <0.05), so it can be concluded that there is a significant relationship between anxiety levels with the incidence of oral candidiasis in the elderly. Oral candidiasis in the elderly if not treated seriously will be one of the causes of stomatognathic dysfunction so that the elderly find it difficult to eat, swallow, talk and taste disorders which will thoroughly cause discomfort and pain in the mouth. Keywords: Anxiety, Elderly, Oral candidiasis